A multi-interfacial FeOOH@NiCo2O4 heterojunction as a highly efficient bifunctional electrocatalyst for overall water splitting. Issue 37 (21st September 2020) - Cao, Xi; Sang, Yan; Wang, Lvxuan; Ding, Gaofei; Yu, Runhan; Geng, Baoyou
Abstract : Multi-interfacial FeOOH@NiCo2 O4 hybrid nanoflowers are successfully prepared by a two-step hydrothermal method. The as-obtained sample can be used as an efficient and stable dual-function electrocatalyst for overall water splitting. Abstract : Electrocatalytic water decomposition is the key to sustainable energy, and the design and synthesis of cost-effective electrocatalysts is the main objective of electrocatalytic water splitting. In this paper, multi-interfacial FeOOH@NiCo2 O4 hybrid nanoflowers are prepared through a two-step hydrothermal reaction. In such heterostructures, NiCo2 O4 nanoflowers are coated with a layer of FeOOH nanoparticles. In addition, the obtained electrocatalyst could provide abundant electroactive sites and the formation of FeOOH@NiCo2 O4 nanointerfaces can also improve the charge transfer rate. As a result, under the HER and OER conditions, the prepared catalysts show an outstanding electrocatalytic performance. Moreover, in a two-electrode water splitting system, the FeOOH@NiCo2 O4 heterostructure, as a dual-function electrocatalyst, needs a cell voltage of only 1.58 V at a current density of 10 mA cm −2 . This study provides a facile and feasible method to construct different kinds of heterostructures as bifunctional electrocatalysts with multiple interfaces by a simple hydrothermal method.